Liar's key [large type] - Neggers, Carla (Neggers, Carla. Sharpe & Donovan novel., 2016)
An FBI legend, a mysterious antiquities specialist and a brazen art thief draw top FBI agents Emma Sharpe and Colin Donovan into a complex web of blackmail, greed and murder in this eagerly awaited new novel in the highly acclaimed Sharpe & Donovan series.